Balinese Phonological Interference in English Pronunciation by Denpasar People - Ni Made Widekusuma Yanti (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2022)
The purpose of this research is to analyse the interference of Balinese Phonological in English Pronunciation by Denpasar people who work in the hospitality field. This phenomenon occurs because of interference between the mother tongue, namely Balinese and a foreign language, namely English. This is because the city of Denpasar is one of the famous tourist attractions throughout the world, so many people work in the hospitality sector. This study uses a qualitative descriptive method with data sources in the form of records of native speakers of Denpasar while speaking English. The data collection was done by asking native speakers of Denpasar, which are Denpasar people who work in hospitality to read English words given and then recorded. The method used in this research is descriptive qualitative design in the form of records. The research methods and techniques consist of the methods and techniques of providing data, the methods and techniques of data analysis, and the methods and techniques of presenting data. After the data were reduced and classified, then the data were transcribed orthographically and phonetically to see the sound errors spoken by native speakers. The results of this study show a number of forms of interference such in the phoneme, such as: [æ] becomes [e], [ɪə] becomes [e], [ɛ] becomes [ə], [eə] becomes [αІ] or [e] or [I], [əʊ] becomes [oː], [ʈʃ] becomes [c], [dʒ] becomes [d], [ŋ] becomes [ng], [eɪ] becomes [e], (r) becomes [r], [f] becomes [p], and [i:] becomes [i]. There are two factors that cause language interference, namely linguistic factor (phonemes) and non-linguistic factors (society and work pressure).